Kinetic and thermodynamic study of phosphate removal from water by adsorption onto () reeds - Arwa Abdelhay; Abeer Al Bsoul; Amani Al-Othman; Nada M Al-Ananzeh; Inshad Jum'h; Ahmed A Al-Taani (Adsorption Science & Technology)
The adsorption of phosphate ion onto natural reed ( Arundo donax ) was studied in this work. The effect of phosphate initial concentration, adsorbent dose, pH, temperature, and salt addition on adsorption uptake was investigated. The results showed that the adsorption uptake is directly proportional to the phosphate ion initial concentration and inversely proportional to the adsorbent's dose and temperature. A maximum adsorption capacity of 16.2 mg/g was observed at neutral pH. The addition of sodium and potassium chlorides has decreased the adsorption uptake. The adsorption isotherms agree better with the Langmuir model. The negative values of (ΔG) and (ΔH) obtained from the thermodynamic study, indicted that the adsorption process is spontaneous and exothermic. The experimental adsorption data were analyzed using three kinetic models: pseudo-first order, pseudo-second order, and intra-particle diffusion model. The pseudo-second-order model presented the best fit with a determination coefficient ( R 2 ) higher than 0.99 and a minimum normalized standard deviation.